Quality of professional life and its association with emotional well-being among COVID-19 physicians and nurses - Reza Azizkhani; Azita Azimi Meibody; Ahmad Sadeghi; Gloria Meibody-Tabar; Fleuria Flechon-Meibody; Behrooz Ataei; Soheila Kouhestani (Advanced Biomedical Research, 2023)
Background: The present study was to compare the professional quality of life (ProQOL) and its association with the emotional well-being among the physicians and nurses in contact with COVID-19 patients in Iran and France. Materials and Methods: The study was performed on 903 nurses and physicians in contact with COVID-19 patients in Iran and France.he subjects completed their demographics online and then answered questions addressing their job stress and emotion associated with their contact with COVID-19 patients and ProQOL. Finally, the collected data were analyzed using the SPSS software (ver. 25). Results: According to the results of the present study, the degree of contact with COVID-19 patients had a significant role in compassion satisfaction, burnout, and compassion fatigue, with the coefficient effects of 0.459, 0.688, and 0.433, respectively (P < 0.05). The emotional well-being had a significant role in increasing compassion satisfaction (B = 0.505, P < 0.05). Conclusion: According to the results of the present study, factors such as contact with a COVID-19 patient, emotional well-being, gender, and marital status had a significant effect on dimensions of ProQOL in both Iran and France. Considering that the entire focus of the physicians and nurses is on the health of COVID-19 patients and they have no concentration on improving their emotional state, it seems that supporting them in terms of psychological self-care and considering its indirect impact on the quality of professional performance are of particular significance.